2020
DOI: 10.1007/s00395-020-00831-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic background influences expression and function of the cation channel TRPM4 in the mouse heart

Abstract: Transient receptor potential melastatin 4 (TRPM4) cation channels act in cardiomyocytes as a negative modulator of the L-type Ca2+ current. Ubiquitous Trpm4 deletion in mice leads to an increased β-adrenergic inotropy in healthy mice as well as after myocardial infarction. In this study, we set out to investigate cardiac inotropy in mice with cardiomyocyte-specific Trpm4 deletion. The results guided us to investigate the relevance of TRPM4 for catecholamine-evoked Ca2+ signaling in cardiomyocytes and inotropy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…In vitro studies on isolated cardiomyocytes indicated that TRPM4 deficiency is associated with a faster repolarization of the action potential and an increased Ca 2+ influx via L-type channels with isoproterenol stimulation [ 23 ]. Recently, we could show that the increased ISO-evoked inotropy and elevated Ca 2+ transient can only be observed in TRPM4-deficeint mice on the 129SvJ genetic background and the TRPM4 protein expression level is about 80% higher in wild-type 129SvJ mice than in mice with C57B/6N background [ 26 ]. The results of this study indicate that the relevance of TRPM4 for cardiac contractility depends on homeostatic TRPM4 expression levels or the genetic background of different mouse strains.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies on isolated cardiomyocytes indicated that TRPM4 deficiency is associated with a faster repolarization of the action potential and an increased Ca 2+ influx via L-type channels with isoproterenol stimulation [ 23 ]. Recently, we could show that the increased ISO-evoked inotropy and elevated Ca 2+ transient can only be observed in TRPM4-deficeint mice on the 129SvJ genetic background and the TRPM4 protein expression level is about 80% higher in wild-type 129SvJ mice than in mice with C57B/6N background [ 26 ]. The results of this study indicate that the relevance of TRPM4 for cardiac contractility depends on homeostatic TRPM4 expression levels or the genetic background of different mouse strains.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, strain-dependent differences were observed in that the overall placental expression of Trpm4 was higher in the mixed BL6/129S background. Although no subfertile phenotype is reported for TRPM4 knockout mice so far with either 129/Svj or C57BL/6J background, it is interesting to note that strain-specific cardiac phenotypes were observed [58][59][60][61][62]. While the entire placental Trpm4 levels were above threshold, spatial FISH expression studies revealed very low expression in the placenta.…”
Section: A Role For Trp Channels In Cellular Physiologymentioning
confidence: 89%
“…The reason for this difference can be the use of Wistar (or Wistar-Kyoto) rats in previous papers [43,147] while Sprague-Dawley rats have been used more recently [44,127]. Indeed, at least in mice, TRPM4 protein expression was about 80% higher in animals with a 129SvJ background versus a C57Bl/6N background [152]. Moreover, on the functional level, increased β-adrenergic inotropy was detected in global TRPM4-deficient 129SvJ mice, but the inotropic response was unaltered in C57Bl/6N mice with both global and cardiomyocyte-specific TRPM4 deletion [152].…”
Section: The Contribution Of Trpm4 To Ventricular Electrophysiologymentioning
confidence: 99%